Thermoplastic resin composition containing carbon nanotubes and a thermoplastic resin

JP7639453B2Active Publication Date: 2025-03-05OSAKA SODA CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021053721
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-26
Publication Date
2025-03-05
Estimated Expiration
2041-03-26

AI Technical Summary

Benefits of technology

【0011】 本発明によれば、カーボンナノチューブを含むにも関わらず、カーボンナノチューブを含まない場合と比較して、機械的強度が高い、熱可塑性樹脂組成物を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007639453000002
    Figure 0007639453000002
  • Figure 0007639453000003
    Figure 0007639453000003
  • Figure 0007639453000004
    Figure 0007639453000004
Patent Text Reader

Abstract

To provide a thermoplastic resin composition having higher mechanical strength though containing a carbon nanotube compared to the case of containing no carbon nanotube.SOLUTION: A thermoplastic resin composition contains a carbon nanotube and a thermoplastic resin, wherein a percentage content of the carbon nanotube of the thermoplastic resin composition is 0.01 mass% or more and less than 0.07 mass%, an average outer diameter of the carbon nanotube is 3.0 nm or less, and when the surface of the thermoplastic resin composition is observed with a range of 10 mm×10 mm at a magnification of 200 times using an optical microscope, an aggregate of the carbon nanotube having a maximum diameter of 50 μm or more is not observed.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thermoplastic resin composition comprising carbon nanotubes and a thermoplastic resin. [Background technology]

[0002] Conventionally, electrical and electronic components, such as semiconductor components such as IC chips, hard disks, and silicon wafers, as well as the materials used to handle these components (e.g., carrier trays, IC sockets, connectors, and wafer tweezers), have the problem of being electrically destroyed when charged with static electricity.

[0003] As members that suppress electrical breakdown due to static electricity, antistatic molded articles made by adding conductive materials such as carbon black, ketjen black, and acetylene black to a resin composition are known.

[0004] For example, Patent Document 1 discloses a composite material obtained by processing a resin composition containing a thermoplastic resin, multi-walled carbon nanotubes, and a reinforcing material, in which the multi-walled carbon nanotubes have an average diameter of 10 nm or more, the walls of the multi-walled carbon nanotubes are composed of 10 or more layers of graphene, the Id / Ig ratio of the multi-walled carbon nanotubes is 1 or less, and the carbon nanotubes remaining in the composite have a length residual ratio defined by the following mathematical formula of 40% or more. Length remaining rate (%) = (content of carbon nanotubes with a length of 500 nm or more among carbon nanotubes remaining in the composite) / (content of carbon nanotubes in the composite) × 100 [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Special Publication No. 2017-512847 Summary of the Invention [Problem to be solved by the invention]

[0006] A thermoplastic resin composition to which an inorganic conductive material has been added has a problem in that it has a reduced mechanical strength compared to a thermoplastic resin to which an inorganic conductive material has not been added.

[0007] Under these circumstances, a main object of the present invention is to provide a thermoplastic resin composition that contains carbon nanotubes but has higher mechanical strength than a thermoplastic resin composition that does not contain carbon nanotubes. [Means for solving the problem]

[0008] The present inventors have conducted extensive research to solve the above problems, and as a result, have unexpectedly discovered that, in a thermoplastic resin composition containing carbon nanotubes and a thermoplastic resin, by using carbon nanotubes having a predetermined average outer diameter, setting the content of the carbon nanotubes in the thermoplastic resin composition within a predetermined range, and further dispersing the carbon nanotubes so that no aggregates of the carbon nanotubes having a maximum diameter of 50 μm or more are observed when observing the surface of the thermoplastic resin composition in an area of ​​10 mm×10 mm at a magnification of 200 times using an optical microscope, the obtained thermoplastic resin composition has higher mechanical strength than a composition not containing carbon nanotubes, despite containing carbon nanotubes.

[0009] The present disclosure has been completed through further investigation based on the above findings.

[0010] That is, the present invention can be described as follows. Item 1. A thermoplastic resin composition comprising carbon nanotubes and a thermoplastic resin, The content of carbon nanotubes in the thermoplastic resin composition is 0.01% by mass or more and less than 0.07% by mass, The carbon nanotubes have an average outer diameter of 3.0 nm or less, A thermoplastic resin composition, wherein when the surface of the thermoplastic resin composition is observed using an optical microscope at a magnification of 200 times over an area of ​​10 mm x 10 mm, no aggregates of the carbon nanotubes having a maximum diameter of 50 μm or more are observed. Item 2. The thermoplastic resin composition according to item 1, wherein the carbon nanotubes have a peak intensity ratio G / D of G band to D band of 30 or more in a Raman spectrum at an excitation wavelength of 532 nm measured by a resonance Raman scattering method. Item 3. The thermoplastic resin composition according to Item 1 or 2, wherein the carbon nanotubes have a viscosity of 2.0 Pa·s or more in a carbon nanotube dispersion as measured by the following measurement method. <Method of measuring viscosity> 40 mg of carbon nanotubes and 200 g of a chloroform solution containing 10% polycarbonate resin are mixed to prepare a carbon nanotube dispersion with a concentration of 0.2% by mass. The dispersion is measured using a rheometer at a temperature of 30°C and a shear rate of 10 s. -1 The viscosity of the carbon nanotube dispersion is measured under the conditions of cone plate: C60 / 2. Item 4. The thermoplastic resin composition according to any one of Items 1 to 3, which is an extrusion molded article. Item 5. The thermoplastic resin composition according to any one of Items 1 to 4, which is an electric part or an electronic part. Effect of the Invention

[0011] According to the present invention, it is possible to provide a thermoplastic resin composition which, despite containing carbon nanotubes, has higher mechanical strength than a composition not containing carbon nanotubes. [Brief description of the drawings]

[0012] [Figure 1a] 1 is an image obtained by observing the surface of the thermoplastic resin composition obtained in Example 1A using an optical microscope at a magnification of 200 times. [Figure 1b] 1 is an image obtained by observing the surface of the thermoplastic resin composition obtained in Example 1B using an optical microscope at a magnification of 200 times. [Figure 1c] 1 is an image obtained by observing the surface of the thermoplastic resin composition obtained in Example 1C using an optical microscope at a magnification of 200 times. [Diagram 2] 1 is an image obtained by observing the surface of the thermoplastic resin composition obtained in Comparative Example 1 using an optical microscope at a magnification of 200 times. [Figure 3a] 1 is an image obtained by observing the surface of the thermoplastic resin composition obtained in Comparative Example 2A using an optical microscope at a magnification of 200 times. [Figure 3b] 1 is an image obtained by observing the surface of the thermoplastic resin composition obtained in Comparative Example 2B using an optical microscope at a magnification of 200 times. [Figure 3c] 1 is an image obtained by observing the surface of the thermoplastic resin composition obtained in Comparative Example 2C using an optical microscope at a magnification of 200 times. [Figure 3d] 1 is an image obtained by observing the surface of the thermoplastic resin composition obtained in Comparative Example 2D with an optical microscope at a magnification of 200 times. [Figure 4a] 1 is an image obtained by observing the surface of the thermoplastic resin composition obtained in Comparative Example 3A using an optical microscope at a magnification of 200 times. [Figure 4b] 1 is an image obtained by observing the surface of the thermoplastic resin composition obtained in Comparative Example 3B with an optical microscope at a magnification of 200 times. [Figure 4c] 1 is an image obtained by observing the surface of the thermoplastic resin composition obtained in Comparative Example 3C using an optical microscope at a magnification of 200 times. [Figure 4d] 1 is an image obtained by observing the surface of the thermoplastic resin composition obtained in Comparative Example 3D using an optical microscope at a magnification of 200 times. [Figure 5a] 1 is an image obtained by observing the surface of the thermoplastic resin composition obtained in Comparative Example 4A using an optical microscope at a magnification of 200 times. [Figure 5b] 1 is an image obtained by observing the surface of the thermoplastic resin composition obtained in Comparative Example 4B with an optical microscope at a magnification of 200 times. [Figure 5c] 1 is an image obtained by observing the surface of the thermoplastic resin composition obtained in Comparative Example 4C using an optical microscope at a magnification of 200 times. [Figure 5d] 1 is an image obtained by observing the surface of the thermoplastic resin composition obtained in Comparative Example 4D using an optical microscope at a magnification of 200 times. [Figure 6] 1 is a graph showing the results of tensile tests in the MD direction of the thermoplastic resin compositions obtained in Examples 1A to 1C and Comparative Example 1. [Figure 7] 2 is a graph showing the results of a tensile test in the MD direction of the thermoplastic resin composition obtained in Reference Example 1. [Figure 8] 1 is a graph showing the results of a tensile test in the MD direction of the thermoplastic resin composition obtained in Reference Example 2. [Figure 9] 1 is a graph showing the results of a tensile test in the MD direction of the thermoplastic resin composition obtained in Reference Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] 1.Thermoplastic resin composition The thermoplastic resin composition of the present invention is a thermoplastic resin composition containing carbon nanotubes and a thermoplastic resin. The carbon nanotube content of the thermoplastic resin composition of the present invention is 0.01% by mass or more and less than 0.07% by mass, and the average outer diameter of the carbon nanotubes is 3.0 nm or less. Furthermore, when the surface of the thermoplastic resin composition of the present invention is observed in an area of ​​10 mm x 10 mm at a magnification of 200 times using an optical microscope, no aggregates of the carbon nanotubes having a maximum diameter of 50 μm or more are observed. The thermoplastic resin composition of the present invention has these characteristics, and thus exhibits a characteristic of having high mechanical strength compared to a case where no carbon nanotubes are included, despite containing carbon nanotubes. The thermoplastic resin composition of the present invention will be described in detail below.

[0014] In this specification, a numerical value connected with "~" means a numerical range including the numerical values ​​before and after "~" as the lower limit and upper limit. When multiple lower limit values ​​and multiple upper limit values ​​are listed separately, any lower limit value and upper limit value can be selected and connected with "~".

[0015] In the thermoplastic resin composition of the present invention, the origin (manufacturing method) of the carbon nanotubes is not limited, and the carbon nanotubes may be manufactured by any manufacturing method as long as the effects of the present invention are achieved. Examples of the manufacturing method of carbon nanotubes include an arc discharge method, a laser evaporation method, and a chemical vapor deposition method (CVD) method, and the chemical vapor deposition method (CVD) method is preferable. In addition, the type of carbon nanotubes is not particularly limited, and may be a single-walled carbon nanotube, a double-walled carbon nanotube, or a multi-walled carbon nanotube. From the viewpoint of suitably exerting the effects of the present invention, the carbon nanotubes are preferably single-walled carbon nanotubes. The carbon nanotubes contained in the thermoplastic resin composition of the present invention may be one type or two or more types.

[0016] The average outer diameter of the carbon nanotubes is 3.0 nm or less. From the viewpoint of more suitably achieving the effects of the present invention, the average outer diameter of the carbon nanotubes is preferably 2.5 nm or less. The average outer diameter of the carbon nanotubes is, for example, 0.5 nm or more, preferably 1.0 nm or more. The average outer diameter of the carbon nanotubes is a value measured by the following method.

[0017] <Average outer diameter of carbon nanotubes> The outer diameter of 100 carbon nanotubes can be measured using a Raman spectrometer and a transmission electron microscope, and the average value can be used as the outer diameter.

[0018] The length of the carbon nanotubes is not particularly limited, but from the viewpoint of more suitably achieving the effects of the present invention, the lower limit may be, for example, 0.001 mm or more, 0.03 mm or more, 0.06 mm or more, 0.1 mm or more, 0.5 mm or more, 1.0 mm or more, 2.0 mm or more, 5.0 mm or more, 10 mm or more, 50 mm or more, and the upper limit may be, for example, 100 mm or less. In the thermoplastic resin composition of the present invention, the carbon nanotubes may be present in a bundled state (bundled state) by being aggregated together to have these lengths, or may be present alone to have these lengths.

[0019] In order to more suitably achieve the effects of the present invention, the carbon nanotube is preferably a carbon nanotube having a G band (1590 cm ) in a Raman spectrum at an excitation wavelength of 532 nm measured by a resonance Raman scattering method. -1 around 1300 cm -1 The peak intensity ratio G / D of the carbon nanotube (near the peak intensity ratio G / D of the carbon nanotube) is preferably 30 or more, more preferably 35 or more. The peak intensity ratio G / D is, for example, 200 or less. The higher the peak intensity ratio G / D of the carbon nanotube, the fewer the defects in the carbon nanotube structure. Therefore, when the above range is satisfied, it is a preferred example from the viewpoint of producing a thermoplastic resin composition in which no aggregates of the carbon nanotubes having a maximum diameter of 50 μm or more are observed when the surface of the thermoplastic resin composition is observed in an area of ​​10 mm x 10 mm at a magnification of 200 times using an optical microscope. In this application, the "peak intensity ratio" means the "height ratio".

[0020] The carbon nanotubes preferably have a viscosity of 2.0 Pa s or more, more preferably 2.2 Pa s or more, and even more preferably 3.0 Pa s or more, as measured by the following method. The upper limit of the viscosity is, for example, 10.0 Pa s or less, and preferably 8.0 Pa s or less.

[0021] <Method of measuring viscosity> 40 mg of carbon nanotubes and 200 g of a chloroform solution containing 10% by mass of polycarbonate resin (Teijin Panlite L1225Y) are mixed to prepare a carbon nanotube dispersion with a concentration of 0.2% by mass. The dispersion is measured using a rheometer (Thermo Scientific, model number "HAAKE MARS III") at a temperature of 30°C and a shear rate of 10 s. -1 The viscosity of the carbon nanotube dispersion is measured under the conditions of cone plate: C60 / 2.

[0022] Further, the carbon nanotube has an amount (atomic %) of functional groups introduced based on the spectrum (O1s) due to the 1s orbital of oxygen atoms, measured by XPS (X-ray photoelectron spectroscopy) under the following measurement conditions, of preferably 0.8 atomic % or less, more preferably 0.7 atomic % or less, and further preferably 0.5 atomic % or less. The lower limit of the amount of functional groups introduced can be, for example, 0 atomic %, 0.01 atomic % or more, etc.

[0023] <Measurement of the amount of functional groups introduced into carbon nanotubes using XPS> The amount of oxygen functional groups introduced is determined by elemental analysis of the carbon nanotube surface based on X-ray photoelectron spectroscopy (XPS·ESCA) using an AXIS-ULTRA DLD X-ray photoelectron spectrometer manufactured by KURATOS and Al-Kα as the X-ray source.

[0024] In the thermoplastic resin composition of the present invention, the carbon nanotube content is 0.01 to 0.07% by mass. From the viewpoint of more suitably achieving the effects of the present invention, the carbon nanotube content is preferably 0.011% by mass or more, more preferably 0.012% by mass or more, and is preferably 0.055% by mass or less, more preferably 0.050% by mass or less.

[0025] In the thermoplastic resin composition of the present invention, when the surface of the thermoplastic resin composition is observed in a range of 10 mm x 10 mm at a magnification of 200 times using an optical microscope, no aggregates of carbon nanotubes having a maximum diameter of 50 μm or more are observed. In the thermoplastic resin composition of the present invention, in order to increase the mechanical strength compared to the case where carbon nanotubes are not included, despite the inclusion of carbon nanotubes, the specified carbon nanotubes need to be highly dispersed in this manner. In order to prevent the observation of aggregates of carbon nanotubes having a maximum diameter of 50 μm or more in the thermoplastic resin composition, it is preferable to use the specified carbon nanotubes and further adopt the manufacturing method of the thermoplastic resin composition of the present invention described later. In addition, for example, in mixing the carbon nanotubes with the thermoplastic resin, it is preferable to reduce the shear rate to suppress the cutting of the carbon nanotubes. The method for observing the aggregates of carbon nanotubes is as described in the examples.

[0026] From the viewpoint of more suitably exerting the effects of the present invention, when the surface of the thermoplastic resin composition of the present invention is observed using an optical microscope at a magnification of 200 times over an area of ​​10 mm x 10 mm, it is preferable that no agglomerates of carbon nanotubes having a maximum diameter of 40 μm or more are observed, and it is even more preferable that no agglomerates of carbon nanotubes having a maximum diameter of 30 μm or more are observed.

[0027] In the thermoplastic resin composition of the present invention, the thermoplastic resin is not particularly limited. From the viewpoint of more suitably achieving the effects of the present invention, the standard molding temperature of the thermoplastic resin is 200°C or higher, preferably 220°C or higher, more preferably 230°C or higher. The standard molding temperature of the thermoplastic resin is a temperature empirically found in general resin molding and set in a molding machine, for example, 210°C for polystyrene, 240°C for polyethylene terephthalate, 200°C for polyethylene, 210°C for polypropylene, 240°C for polybutylene terephthalate, 280°C for polycarbonate, 230°C for acrylonitrile-butadiene-styrene copolymer (ABS), and 250°C for polyamide.

[0028] Specific examples of preferred thermoplastic resins include polyethylene resins, polypropylene resins, polystyrene resins, rubber-modified polystyrene resins, acrylonitrile-butadiene-styrene (ABS) resins, acrylonitrile-styrene (AS) resins, polymethyl methacrylate resins, acrylic resins, polyvinyl chloride resins, polyvinylidene chloride resins, polyethylene terephthalate resins, ethylene vinyl alcohol resins, cellulose acetate resins, ionomer resins, polyacrylonitrile resins, polyamide resins, polyacetal resins, polybutylene terephthalate resins, polylactic acid resins, polyphenylene ether resins, modified polyphenylene ether resins, polycarbonate resins, polysulfone resins, polyphenylene sulfide resins, polyetherimide resins, polyethersulfone resins, polyarylate resins, thermoplastic polyimide resins, polyamideimide resins, polyetheretherketone resins, polyketone resins, liquid crystal polyester resins, fluororesins, syndiotactic polystyrene resins, and cyclic polyolefin resins. These thermoplastic resins can be used alone or in combination of two or more.

[0029] In the thermoplastic resin composition of the present invention, the total content of the thermoplastic resin and the carbon nanotubes is, for example, 90.0% by mass or more and 100% by mass or less, and may be 97.0% by mass or less, or may be 95.0% by mass or less. The thermoplastic resin composition of the present invention may be a thermoplastic resin composition containing substantially only carbon nanotubes and a thermoplastic resin.

[0030] In addition, as long as the effects of the present invention are not impaired, other compounding agents may be contained, and can be appropriately selected from known ones depending on the application of the extrusion molded article of the present invention, such as antioxidants, heat stabilizers, light stabilizers, ultraviolet absorbers, crosslinking agents, pigments, colorants, foaming agents, antistatic agents, flame retardants, lubricants, softeners, tackifiers, plasticizers, mold release agents, deodorants, fragrances, etc. The content of additives contained in the thermoplastic resin composition is preferably 5% by mass or less, more preferably 3% by mass or less.

[0031] The surface resistance of a film formed using the thermoplastic resin composition of the present invention is preferably 10 6 ~10 13 Ω / sq., more preferably 10 6 ~10 12 Ω / sq., and more preferably 10 6 ~10 10 The surface resistance is measured in Ω / sq. by the following method.

[0032] (Surface resistance measurement) Under standard conditions (23°C, 50% RH), a high resistance resistivity meter (e.g., Hiresta-UX MCP-HT800 (manufactured by Mitsubishi Chemical Analytical Co., Ltd.)) is used to press a probe (e.g., USR probe MCP-HTP14) with a load of 1 kg against the surface of a film formed from a thermoplastic resin composition, and the surface resistance value is measured by a constant voltage application / leakage current measurement method.

[0033] The shape of the thermoplastic resin composition of the present invention is not particularly limited. For example, the thermoplastic resin composition of the present invention can be formed into an extrusion molded product by extrusion molding.

[0034] The method for producing the thermoplastic resin composition of the present invention is not particularly limited, but the composition can be suitably produced by the method for producing the thermoplastic resin composition of the present invention described below.

[0035] Applications of the thermoplastic resin composition of the present invention are not particularly limited, and examples thereof include electrical or electronic parts such as semiconductor parts (e.g., IC chips, hard disks, silicon wafers, etc.) and parts for handling semiconductor parts (e.g., carrier trays, IC sockets, connectors, wafer tweezers, etc.).

[0036] 2. Method for producing thermoplastic resin composition The thermoplastic resin composition of the present invention can be produced, for example, by a method comprising the following steps. Step 1: A master batch containing carbon nanotubes having an average outer diameter of 3.0 nm or less and a thermoplastic resin is prepared. Step 2: The master batch prepared in step 1 is mixed with a thermoplastic resin so that the carbon nanotube content is 0.01% by mass or more and less than 0.07% by mass, and the mixture is kneaded at a temperature equal to or higher than the melting point of the thermoplastic resin to prepare a molten thermoplastic resin composition. Step 3: The molten thermoplastic resin composition is molded using a melt extrusion device.

[0037] By employing the method for producing a thermoplastic resin composition of the present invention, the above-mentioned thermoplastic resin composition of the present invention can be produced. In the method for producing a thermoplastic resin composition of the present invention, the carbon nanotubes, the thermoplastic resin, and the like are as described in the above section "1. Thermoplastic resin composition."

[0038] Step 1 is a step of preparing a masterbatch containing carbon nanotubes and a thermoplastic resin. In the method for producing a thermoplastic resin composition of the present invention, a masterbatch having the predetermined content is prepared, and in step 2 described below, the masterbatch and a thermoplastic resin are mixed and melted so that the carbon nanotube content falls within a predetermined range. The carbon nanotube content in the masterbatch is preferably 0.1% by mass or more and 70% by mass or less. By using a masterbatch in which the carbon nanotubes are adjusted to a predetermined content, and mixing and melting the masterbatch and a thermoplastic resin so that the carbon nanotubes fall within the predetermined content, the carbon nanotubes are uniformly dispersed in the thermoplastic resin composition of the present invention, and the formation of aggregates is easily suppressed.

[0039] In order to more suitably exert the effects of the present invention, the carbon nanotube content in the master batch is preferably 0.1 to 70 mass %, and more preferably 0.5 to 50 mass %.

[0040] There is no particular limitation on the method for producing the masterbatch, but by dispersing carbon nanotubes in a dispersion medium in which a thermoplastic resin is dissolved in a solvent (e.g., an organic solvent such as chloroform), a carbon nanotube dispersion liquid free of visible aggregates can be prepared, and by distilling off the solvent from this dispersion liquid, a masterbatch in which the carbon nanotubes are uniformly dispersed can be produced. The particle size of the masterbatch is preferably, for example, about 0.01 mm to 3.0 mm.

[0041] The method for producing a carbon nanotube dispersion liquid can be carried out using a conventionally known dispersion device, and the device can be selected depending on the viscosity of the dispersion medium or the viscosity expected in the carbon nanotube dispersion liquid state. Examples of the dispersion device include a homogenizer, a bead mill, a ball mill, a basket mill, an attrition mill, a universal mixer, a clear mixer, an ultrasonic wave, a jet mill, and a shear dispersion treatment. For the shear dispersion treatment, a product name "Nano Jet Pal JN20" (manufactured by Jokou Co., Ltd.) or a product name "Nano Vaita L-ES" (manufactured by Yoshida Kikai Kogyo Co., Ltd.) can be used.

[0042] Preferred dispersion media include, but are not limited to, water, halogen-based solvents, alcohols, phenols, amides, allyls, ketones, and rubber plasticizers, or mixtures of at least two of these.

[0043] Examples of halogen-based solvents include chloroform, dichloromethane, etc. Examples of alcohols include methanol, ethanol, isopropyl alcohol, n-butyl alcohol, polycarbonate diol, etc. Examples of phenols include bisphenol, trisphenol, polyphenol, etc.

[0044] Examples of amides include N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, 1,3-dimethyl-2-imidazolidinone, N,N-dimethylformamide, N,N-diethylformamide, N,N-dimethylacetamide, N,N-diethylacetamide, and dimethylsulfoxide. Examples of allyls include diallyl phthalate, triallyl trimesate, triallyl trimellitate, and 1,3,5,7-tetraallylnaphthalene.

[0045] Examples of ketones include acetone, methyl ethyl ketone, and methyl isobutyl ketone.

[0046] Examples of rubber plasticizers include phthalic acid derivatives, tetrahydrophthalic acid derivatives, adipic acid derivatives, azelaic acid derivatives, sebacic acid derivatives, dodecane-2-acid derivatives, maleic acid derivatives, fumaric acid derivatives, trimellitic acid derivatives, pyromellitic acid derivatives, citric acid derivatives, oleic acid derivatives, ricinoleic acid derivatives, stearic acid derivatives, fatty acid derivatives, sulfonic acid derivatives, phosphoric acid derivatives, glutaric acid derivatives, glycolic acid derivatives, glycerin derivatives, paraffin derivatives, epoxy derivatives, monoester-based plasticizers, polyester-based plasticizers, polyether-based plasticizers, paraffin-based mineral oils, naphthene-based mineral oils, aromatic mineral oils, vegetable oil-based plasticizers, and other plasticizers.

[0047] Step 2 is a step of mixing the master batch prepared in step 1 with a thermoplastic resin so that the carbon nanotube content is 0.01% by mass or more and less than 0.07% by mass, and kneading at a temperature equal to or higher than the melting point of the thermoplastic resin to prepare a molten thermoplastic resin composition. If the thermoplastic resin used in the master batch and the thermoplastic resin mixed with the master batch are the same, an extrusion molded product containing a single thermoplastic resin is obtained. In general, an extrusion molded product containing a single thermoplastic resin is used.

[0048] The kneading method is not particularly limited, and can be produced by mixing (kneading) various materials. The mixing (kneading) method is not particularly limited, and examples thereof include melt kneading methods using mixers such as open rolls, intensive mixers, internal mixers, co-kneaders, continuous kneaders with twin-screw rotors, and extruders. As the extruder, either a single-screw or twin-screw extruder can be used. As described above, in mixing the carbon nanotubes and the thermoplastic resin, it is preferable to reduce the shear rate to prevent the carbon nanotubes from being cut.

[0049] The molten thermoplastic resin composition prepared by kneading may be subjected to step 3 as it is, or may be cooled and solidified once to form pellets, and in step 3, the pellets of the thermoplastic resin composition may be melted again and subjected to extrusion molding.

[0050] In step 3, the molten thermoplastic resin composition is extruded to form a film. Specific methods for forming the film include, for example, cast molding in which the thermoplastic resin composition in a fluid state is poured into a mold or surface and solidified, extrusion molding in which the thermoplastic resin composition is heated, softened, and extruded using an extruder, inflation molding in which the molten thermoplastic resin composition is extruded through an annular hole to form a cylindrical film, and calendar molding in which the thermoplastic resin composition is rolled between two heated rolls. EXAMPLES

[0051] The present invention will be described in more detail below with reference to examples, but the following examples are not intended to limit the scope of the invention. In the present invention, "parts" refers to "parts by mass" and "%" refers to "% by mass".

[0052] <Measurement of peak intensity ratio G / D of carbon nanotubes> The carbon nanotubes (No. 1, No. 2, No. 3, and No. 4) used in the examples and comparative examples were measured using a Raman spectrometer by resonance Raman scattering (excitation wavelength 532 nm). In the Raman spectrum, the G band (1590 cm -1 around 1300 cm -1 The peak intensity ratios of the two peaks (around 100 nm) were calculated. The results are shown in Table 1.

[0053] <Measurement of the amount of functional groups introduced into carbon nanotubes using XPS> The amount of functional groups introduced (atomic%) based on the spectrum (O1s) due to the 1s orbital of oxygen atoms was measured for each of the carbon nanotubes (No. 1, No. 2, No. 3, and No. 4) used in the examples and comparative examples by XPS (X-ray photoelectron spectroscopy). Specifically, the amount of oxygen functional groups introduced was determined by elemental analysis of the carbon nanotube surface using Al-Kα as an X-ray source with a KURATOS AXIS-ULTRA DLD X-ray photoelectron spectrometer based on X-ray electron spectroscopy (XPS·ESCA). The results are shown in Table 1.

[0054] <Viscosity measurement of carbon nanotube dispersion> The viscosity of the carbon nanotube dispersion liquid was measured for each of the carbon nanotubes (No. 1, No. 2, No. 3, and No. 4) used in the examples and comparative examples by the following measurement method. 40 mg of carbon nanotubes was mixed with 200 g of a chloroform solution containing 10% by mass of polycarbonate resin to prepare a 0.2% by mass carbon nanotube dispersion liquid. The viscosity was measured using a rheometer (manufactured by Thermo Scientific, model number "HAAKE MARS III") at a 30°C environment and a shear rate of 10 s -1 The viscosity of the carbon nanotube dispersion was measured under the conditions of cone plate: C60 / 2. The results are shown in Table 1.

[0055] The physical properties of the carbon nanotubes (No. 1, No. 2, No. 3, No. 4) used in the examples and comparative examples are shown in Table 1 below.

[0056] [Table 1]

[0057] <Tensile test> The thermoplastic resin compositions of the Examples, Comparative Examples, and Reference Examples were subjected to tensile tests by the following method. A film (200 mm long, 100 mm wide, 50 μm thick) of each thermoplastic resin composition was cut to obtain a test piece of MD (40 mm long) × TD (5 mm wide). Next, a tensile test was performed using a small tensile / compression material testing machine 180E0 manufactured by Imoto Manufacturing Co., Ltd. under the measurement conditions of a tensile speed of 1 mm / min and a chuck distance of 35 mm. Graphs obtained from the tensile tests (graphs showing the relationship between tensile stress and strain in the MD direction (SS curves)) are shown in Figs. 6 to 9.

[0058] <Observation of the Surface of Thermoplastic Resin Composition> Using an optical microscope (Keyence Digital Microscope VHX-6000), the surfaces of the thermoplastic resin compositions of the Examples and Comparative Examples were observed in an area of ​​10 mm x 10 mm at a magnification of 200. The images obtained are shown in Figures 1a to 5d.

[0059] [Examples 1A-1C] and [Comparative Example 1] (Preparation of Carbon Nanotube Dispersion) A carbon nanotube No. 1 (OStube manufactured by Osaka Soda Co., Ltd., having the physical properties described in Table 1) was added to a 10% by mass chloroform solution of polycarbonate resin (manufactured by Teijin, Panlite L-1225Y, standard molding temperature 250°C, glass transition temperature 147°C) to obtain a crude dispersion of carbon nanotubes. At this time, the content of carbon nanotubes in the crude dispersion was 0.1% by mass. Next, each crude dispersion was subjected to a dispersion treatment using Nanovater L-ES (manufactured by Yoshida Kikai Kogyo Co., Ltd.) to produce a carbon nanotube dispersion without visually recognizable aggregates. Next, the chloroform was distilled off and the mixture was pulverized to produce a 3 mm square carbon nanotube-containing polycarbonate resin master batch. At this time, the content of carbon nanotubes in the master batch was 1.0% by mass.

[0060] (Preparation of carbon nanotube-containing pellets) Carbon nanotube-containing pellets were produced as follows. A polycarbonate resin (Teijin, Panlite L-1225Y) and the polycarbonate resin master batch of carbon nanotubes were kneaded at 280°C in a vented twin-screw extruder (model number "TEM-18SS", Toshiba Machine Co., Ltd.) to produce polycarbonate-containing pellets containing carbon nanotubes. At this time, the content of carbon nanotubes in the pellets was 0.01% by mass in Example 1A, 0.025% by mass in Example 1B, 0.05% by mass in Example 1C, and 0.1% by mass in Comparative Example 1.

[0061] (Production of extrusion molded body) The resulting polycarbonate-containing pellets were each mixed at 280° C. in a T-die extrusion molding machine (model number "GT-20-A", manufactured by Plastics Engineering Research Institute), and then an extruded film having a thickness of 50 μm was produced.

[0062] [Comparative Examples 2A-2D] Except for using No. 2 (ZEONANO SG101 manufactured by Zeon Nano Technology Co., Ltd., having the physical properties shown in Table 1) as the carbon nanotubes, a film-shaped extrusion molding was obtained in the same manner as in Examples 1A to 1C. The carbon nanotube content in the film was 0.01% by mass in Comparative Example 2A, 0.025% by mass in Comparative Example 2B, 0.05% by mass in Comparative Example 2C, and 0.1% by mass in Comparative Example 2D.

[0063] [Comparative Examples 3A-3D] Except for using No. 3 (TUBALL manufactured by Oxal Corporation, having the physical properties shown in Table 1) as the carbon nanotubes, a film-shaped extrusion molding was obtained in the same manner as in Examples 1A to 1C. The carbon nanotube content in the film was 0.01% by mass in Comparative Example 3A, 0.025% by mass in Comparative Example 3B, 0.05% by mass in Comparative Example 3C, and 0.1% by mass in Comparative Example 3D.

[0064] [Comparative Examples 4A-4D] Except for using No. 4 (NC7000 manufactured by Nanosil, having the physical properties shown in Table 1) as the carbon nanotube, a film-shaped extrusion molding was obtained in the same manner as in Examples 1A to 1C. The carbon nanotube content in the film was 0.01% by mass in Comparative Example 4A, 0.025% by mass in Comparative Example 4B, 0.05% by mass in Comparative Example 4C, and 0.1% by mass in Comparative Example 4D.

[0065] [Reference example 1] A film-shaped extrusion molding was obtained in the same manner as in Examples 1A-1C, except that no carbon nanotubes were blended.

[0066] [Reference example 2] (Preparation of Carbon Black-Containing Pellets) Carbon black-containing pellets were produced as follows. Polycarbonate resin (Teijin, Panlite L-1225Y) and "Mitsubishi Chemical carbon black, #960" were kneaded at 280°C in a vented twin-screw extruder (model number "TEM-18SS", Toshiba Machine Co., Ltd.) to produce carbon black-containing polycarbonate-containing pellets. At this time, the carbon black content in the pellets was 0.1% by mass.

[0067] (Production of extrusion molded body) The obtained polycarbonate-containing pellets were kneaded at 280°C in a T-die extrusion molding machine (model number "GT-20-A" manufactured by Plastics Engineering Research Institute) to produce an extruded film with a thickness of 50 μm. The carbon black content in the film was 0.1% by mass.

[0068] [Reference example 3] A film-shaped extrusion molded product was obtained in the same manner as in Reference Example 2, except that "Graphene, N002-PDR, manufactured by Angston Materials Co., Ltd." was used instead of carbon black. The graphene content in the film was 0.1% by mass.

[0069] When the surface of the film-like extrusion moldings of Examples 1A-1C and Comparative Example 1 was observed in a range of 10 mm x 10 mm at a magnification of 200 times using an optical microscope, not a single aggregate of the carbon nanotubes having a maximum diameter of 50 μm or more was observed. Furthermore, not a single aggregate of the carbon nanotubes having a maximum diameter of 30 μm or more was observed. In addition, the film-like extrusion moldings of Examples 1A-1C all had higher mechanical strength (tensile strength) than Reference Example 1 (blank), but the film-like molding of Comparative Example 1 had lower mechanical strength (tensile strength) than Reference Example 1 (blank) and Examples 1A-1C.

[0070] On the other hand, when the surface of the film-like extrusion moldings of Comparative Examples 2A-2D, 3A-3D, and 4A-4D was observed in a range of 10 mm x 10 mm at a magnification of 200 times using an optical microscope, one or more aggregates of the carbon nanotubes with a maximum diameter of 50 μm or more were observed. In addition, when the film-like extrusion moldings of Comparative Examples 2A-2D, 3A-3D, and 4A-4D were subjected to a tensile test, the film broke at the carbon nanotube aggregate immediately after the start of the measurement in each film, and the test could not be continued. From this, it was expected that the mechanical strength (tensile strength) of the film-like extrusion moldings of Comparative Examples 2A-2D, 3A-3D, and 4A-4D was lower than that of Reference Example 1 (blank).

[0071] The film-like extrusion molded products of Reference Examples 2 and 3, in which carbon black or graphene was blended, had lower mechanical strength (tensile strength) than Reference Example 1 (blank).

Claims

1. A thermoplastic resin composition comprising carbon nanotubes and a thermoplastic resin, The content of carbon nanotubes in the thermoplastic resin composition is 0.01% by mass or more and less than 0.07% by mass, The carbon nanotubes have an average outer diameter of 3.0 nm or less, When elemental analysis of the carbon nanotube surface is performed by XPS (X-ray photoelectron spectroscopy) using Al-Kα as an X-ray source, the amount of functional groups introduced (atomic %) based on a spectrum (O1s) due to the 1s orbital of oxygen atoms is 0.8 atomic % or less; A thermoplastic resin composition, wherein when the surface of the thermoplastic resin composition is observed using an optical microscope at a magnification of 200 times over an area of ​​10 mm x 10 mm, no aggregates of the carbon nanotubes having a maximum diameter of 50 μm or more are observed.

2. The thermoplastic resin composition according to claim 1, wherein the carbon nanotubes have a peak intensity ratio G / D of G band to D band of 30 or more in a Raman spectrum at an excitation wavelength of 532 nm measured by a resonance Raman scattering method.

3. 3. The thermoplastic resin composition according to claim 1, wherein the carbon nanotubes have a viscosity of 2.0 Pa·s or more in a carbon nanotube dispersion liquid measured by the following measurement method. <Method of measuring viscosity> 40 mg of carbon nanotubes and 200 g of a chloroform solution containing 10% by mass of polycarbonate resin are mixed to prepare a carbon nanotube dispersion having a concentration of 0.2% by mass. The dispersion is measured using a rheometer at a temperature of 30° C. and a shear rate of 10 s -1 The viscosity of the carbon nanotube dispersion is measured under the conditions of: cone plate: C60 / 2.

4. The thermoplastic resin composition according to any one of claims 1 to 3, which is an extrusion molded article.

5. The thermoplastic resin composition according to any one of claims 1 to 4, which is an electric part or an electronic part.

Citation Information

Patent Citations

  • Composite materials with improved mechanical properties and molded articles containing them

    JP2017512847A

  • Thermally conductive composition

    JP2021143249A

  • Electrically conductive polycarbonate compounds

    US20170058105A1

  • Carbon nanotube composite material

    WO2013047796A1

  • Method for manufacturing thermoelectric conversion element and method for producing dispersion for thermoelectric conversion layers

    WO2014157259A1